A Bone-Targeting Enoxacin Delivery System to Eradicate Staphylococcus Aureus-Related Implantation Infections and Bone Loss - Yao, Cong; Zhu, Meisong; Han, Xiuguo; Xu, Qiang; Dai, Min; Nie, Tao; Liu, Xuqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Post-operative infections in orthopaedic implants are severe complications that require urgent solutions. Although conventional antibiotics limit bacterial biofilms formation, they ignore the bone loss caused by osteoclast formation during post-operative orthopaedic implant-related infections. Fortunately, enoxacin exerts dual antibacterial and osteoclast inhibitory effects, playing a pivot in limiting infection and preventing bone loss. However, enoxacin lacks specificity in bone tissue and low bioavailability-relate side effects, which hinders translational practice. Herein, we developed a nanosystem (Eno@MSN-D) based on enoxacin (Eno)-loaded mesoporous silica nanoparticles (MSN), decorated with the eight repeating sequences of aspartate (D-Asp8), and coated with polyethylene glycol (PEG). This Eno@MSN-D delivery nanosystem exhibited both antibacterial and anti-osteoclast properties in vitro. More importantly, Eno@MSN-D allowed the targeted release of enoxacin in infected bone tissues and prevented implant-related infection and bone loss in vivo. Therefore, our work highlights the significance of novel biomaterials that offer new alternatives to treat and prevent orthopaedic staphylococcus aureus-related implantation infections and bone loss.